Humility and the Hoop Dance: A Teacher’s Reflections on Indigenous Knowledge and Power Sharing in the Classroom - Hill, Lauren (The Canadian Journal of Action Research)

(untitled) (Canadian Association of Action Research in Education, 2023)
This research reflects on my collaboration with an Indigenous hoop dancer to respond to the Calls to Action from the final report of the Truth and Reconciliation Commission of Canada. The research engages the Anishinaabeg seven sacred teachings and critical decolonizing pedagogy as theoretical frameworks and qualitative inquiry as methodology. This paper presents partial findings of the research, focusing on my own reflections on humility and its complex connections to power sharing, collaboration, and Indigenous knowledge in the arts. I introduce the “humility pendulum,” which is a conceptual tool that I developed to support my own critical reflection throughout the process.